Coping with Evil in Religion and Culture : Case Studies - Doorn-Harder, Pieternella van, 1956-; Minnema, Lourens. (Currents of Encounter, 2008)
The various Christian, Muslim, traditional (African), and secular (Western) ways of imagining and coping with evil collected in this volume have several things in common. The most crucial perhaps and certainly the most striking aspect is the problem of defining the nature or characteristics of evil as such. Some argue that evil has an essence that remains constant, whereas others say its interpretation depends on time and place. However much religious and secular interpretations of evil may have changed, the human search for sense and meaning never ends. Questions of whom to blame and whom to address-God, the devil, fate, bad luck, or humans-remain at the center of our explanations and our strategies to comprehend, define, counter, or process the evil we do and the evil done to us by people, God, nature, or accident. Using approaches from cultural anthropology, religious studies, theology, philosophy, psychology, and history, the contributors to this volume analyze how several religious and secular traditions imagine and cope with evil.